Impact evaluation of business license simplification in Peru an independent assessment of an International Finance Corporation-supported project. - World Bank. (Washington, D.C. The World Bank, 2012)
This evaluation is about the nature and magnitude of the cost savings and other benefits of business license simplification in one of the central districts of Lima, Peru. IEG asked whether the project?s license simplification reform reduced costs and operating procedures and whether it increased business registration. The project was implemented from 2005 to 2007. Two evaluations done in 2007 and 2008-11 examined, respectively, whether the project led to reductions in time and procedures and whether it led to improved business outcomes. This evaluation reviewed both of those, collected additional data, and drew lessons for future operations. The evidence points to significant reductions in time, monetary costs, and business procedures for businesses that registered to obtain licenses. However, the greater formality of the business environment did not improve the enterprises? access to financing, facilitate investment, or remove invisible barriers to business growth. These results have policy implications for formal business environments. Although there were not large positive effects for enterprise outcomes, enterprise owners and society overall gained through owners spending less time away from their firms to certify and register their firms. Such projects are sometimes promoted as a way to foster dynamic businesses, but the evidence in this report suggests that the more mundane time and cost savings are a significant part of the benefits. These results offer the promise of sharpening the understanding of the circumstances under which reforms may be viewed as a growth engine for a society; they also enable IFC to provide a more focused understanding of reasonable expectations for such projects. Based on these findings, IEG?s evaluation offers several recommendations about follow-up evaluations, investment in data collection, and developing a base of evidence to aid in setting expectations for projects.
Electronic reproduction.
Keywords: Business enterprises -- Licenses -- Peru -- Lima; Electronic books